La Iglesia continental que llegaba al concilio. Eclesiología de los vota de los obispos latinoamericanos para el Concilio Vaticano II (2020)
The article reviews all the proposals (or vota) sent by the Latin American and Caribbean bishops to the Antepreparatory Commission of the Second Vatican Council on subjects that should be discussed by the conciliar assembly. The purpose is to uncover the underlying ecclesiology of the pastors partaking in the council. The text is structured in two parts. A statistical study of the 395 vota or episcopal responses. And, subsequently, a study of all subjects relating to the nature and mission of the Church, so as to go deep into the underlying ecclesiology. Such a research -not thus far undertaken considering all the vota- reveals Latin American and Caribbean bishops not specially original in contents, but showed nevertheless some attitudes and accents which foreshadow the new ecclesiastical disposition which will begin to emerge on the continent as a result of the conciliar experience.